Comparison of journal self-citation rates between some Chinese and non-Chinese international journals. - Zu-Guo Yang (Public Library of Science (PLoS), 2012)
Background The past 3 decades have witnessed a boost in science development in China; in parallel, more and more Chinese scientific journals are indexed by the Journal Citation Reports issued by Thomson Reuters (SCI). Evaluation of the performance of these Chinese SCI journals is necessary and helpful to improve their quality. This study aimed to evaluate these journals by calculating various journal self-citation rates, which are important parameters influencing a journal impact factor. Methodology/principal findings We defined three journal self-citation rates, and studied these rates for 99 Chinese scientific journals, almost exhausting all Chinese SCI journals currently available. Likewise, we selected 99 non-Chinese international (abbreviated as 'world') journals, with each being in the same JCR subject category and having similar impact factors as their Chinese counterparts. Generally, Chinese journals tended to be higher in all the three self-citation rates than world journal counterparts. Particularly, a few Chinese scientific journals had much higher self-citation rates. Conclusions/significance Our results show that generally Chinese scientific journals have higher self-citation rates than those of world journals. Consequently, Chinese scientific journals tend to have lower visibility and are more isolated in the relevant fields. Considering the fact that sciences are rapidly developing in China and so are Chinese scientific journals, we expect that the differences of journal self-citation rates between Chinese and world scientific journals will gradually disappear in the future. Some suggestions to solve the problems are presented.